Diversity and contested social identities in multilingual and multicultural contexts of the University of the Western Cape, South Africa. Issue 6 (17th August 2016) - Banda, Felix; Peck, Amiena
ABSTRACT: We draw on Rampton's Crossing: Language and Ethnicity Among Adolescents (2014. 2nd ed. New York: Routledge) notion of 'crossing' to explore contestations in ethnolinguistic, cultural and racial affiliations at the University of the Western Cape (UWC), a university built for 'Coloureds' in apartheid South Africa, but which rebelled by admitting students of all races and ethnic backgrounds. Using interviews and observation data, we show contestations around Xhosa and Afrikaans as languages for black and coloured solidarity, respectively. We argue that the multilingual and multicultural contexts in place entail that social legitimacy is not achieved through fixed linguistics forms, bounded ethnolinguistic categories and predetermined racial characteristics but in negotiated in-group and out-group codes all of which are part of the students' repertoire. We conclude that diversity is a function of discourses of convergence and divergence as social practice, which give the institution its unique character. The contestations and contradictions thus reflect the democratic conditions on which discourses of diversity are produced and consumed by the multiple socio-cultural range of student populace.